GREEN SUPPLY CHAIN PERFORMANCE BASED ON GREEN BUILDING ASSESSMENT (CASE STUDY OF SUKAWATI ART MARKET CONSTRUCTION STAGE, GIANYAR REGENCY) - Astoeti, Dianisari Rinda; Dwijendra, Ngakan Ketut Acwin (ASTONJADRO, 2021)
Over the last decade the construction industry has made efforts to develop green building practices. With the enactment of PUPR Ministerial Regulation 21 of 2021 concerning Performance Assessment of Green Buildings, the Government requires the Government to implement green construction in every stage of construction, both in planning, development, supervision, operation and maintenance. In addition to planners, contractors have an important role in the principles of green building sustainability. The Sukawati Art Market as a public building has gone through a green building planning certification process by the Ministry of Public Works and Public Housing in 2019. The purpose of this study is to identify and analyze the application of green construction in the implementation of the Sukawati Art Market development focusing on the parameters of the Green Supply Chain. This study begins with the identification of the parameters according to the checklist for the performance assessment of the BGH construction implementation phase for New Buildings. Then proceed with doing a comparison to evaluate the field data obtained with the assessment standard and perform an analysis on the parameters of the green supply chain. The research method used is qualitative which includes case studies of construction implementation and qualitative interviews with the parties involved. The results obtained are that the construction of the Sukawati Art Market has met the criteria as a building that has an environmentally friendly construction process with a total value of 101 points or 61% and is included in the pratama predicate.